Restitution - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2007)
2006 has been a quiet year for the law of restitution in Singapore, with no significant superior court decisions turning on the law of restitution, even though it would appear that claims in restitution are now routinely heard in the subordinate courts. A small number of High Court cases did touch upon points of interest in the law of restitution.